Pembiasaan Shalat Dhuha Dan Mengaji Dalam Menumbuhkan Karakter Religius Anak Di Mi Darus Salam - Moh. Rokib; As'ari; Mahfida Inayati; Madhur M (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2025)
This study aims to describe the role of the habit of dhuha prayer and reciting before lessons in shaping children's religious character in the elementary school environment. The research approach used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation of teachers, students, and principals. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the habit of dhuha prayer and reciting has a significant contribution to the formation of students' religious character, especially in the aspects of discipline, sincerity, responsibility, and spiritual concern. These worship activities not only foster religious awareness, but also strengthen moral values such as honesty, perseverance, and gratitude in daily life. In addition, the support of teachers and the school environment plays an important role in maintaining the consistency of the implementation of religious activities. This study recommends that schools continue to strengthen religious culture by involving all school residents, developing sustainable spiritual development programs, and making religious activities an integral part of national character education.